Rancang Bangun Alat Pembengkok Kawat Metal Jig - Muhammad Yunus; Nanda Pranandita (Universitas Nusantara PGRI Kediri, 2021)
An UMKM (micro, small and medium scale business) in the city of Pangkalpinang, Province of Kep. Bangka Belitung, with the trademark